VAS Pain Analysis Before and After Genicular Nerve Block in Different Types Occupations of Knee Osteoarthritis Patients in Orthopedic Polyclinic Hati Mulia General Hospital Kendari - Febriski Okta Bimantara S; Muhammad Rustam HN; Tien (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2024)
ABSTRACT Background: Knee OA patients suffer from joint pain, stiffness, instability, and swelling. This causes a decrease in the quality of life and daily activities. Knee osteoarthritis is a multifactorial disease, namely modifiable and non-modifiable factors. One of the modifiable risk factors for OA is occupation. One of the therapies for knee OA is Genicular Nerve Block (GNB). Purposes: to determine the correlation between the type of work and VAS of pain before and after genicular nerve block in knee OA patients at the Orthopedic Clinic, Hati Mulia General Hospital, Kendari. Methods: This quasi-experimental research used a one-group pretest-posttest design approach without control. This study has conducted using a questionnaire (informed consent, respondent form, and VAS sheet) from 29 OA patients before and after genicular nerve block (GNB) was performed at the orthopedic polyclinic of Hati Mulia General Hospital for the period November 2021. The dependent variable observed was VAS and the independent variable observed was the type of work. Data analysis used the Spearmen and Wilcoxon statistical test and if p <0.05, it indicated that there was a correlation between the independent and dependent variables. Results: Analysis of the correlation between occupational type and VAS pain before genicular nerve block (GNB) obtained p-value = 0.624, the correlation between occupational type and VAS pain after GNB obtained p-value = 0.716, and the influence before and after GNB on VAS pain obtained p-value = 0.000. Conclusion: There was no correlation between the occupational type and the pain VAS before and after Genicular nerve block (GNB) there was a difference before and after the Genicular nerve block (GNB) on the pain VAS. Keywords: Osteoarthritis, ocupational type, VAS, GNB